Effeminacy in Personal Branding on Social Media - Zulaikha Zulaikha; Ninda Ayu Bistanovasari (Nyimak: Journal of Communication, 2021)
Today, social media is more than just a platform to connect people. Social media can also be a marketing tool for various things, such as daily necessities products, secondary needs, philosophies, social campaigns, and so on. Instagram is one of the most popular social media platforms. The popularity of Instagram among young people is an interesting phenomenon. The very large number of Instagram users in Indonesia causes fierce competition for followers. So, every celebgram content is based on a certain idea. This difference is personal branding for each celebgram in generating replies on Instagram social media. This research aims to study how Indonesian Instagram superstars develop their ‘ngondek’ personal branding. This study uses a qualitative content analysis methodology to examine three accounts, Dhanar Jabro Febiansyah (@brojabrooo), Yoga Arizona (@yogaarizona), and Abdul Kadir (@dkadior). The results of this study indicate that personal branding that is built by celebrities through the impression of ‘Ngondek’ can be the right approach in attracting the attention of netizens on social media. Of course, in building the ‘Ngondek’ personal branding, it also requires research from the ‘Ngondek’ celebgrams in character selection, costume preparation, story concepts, and property preparation.Keywords: Effeminacy, personal branding, social media ABSTRAKDi dunia sekarang ini, media sosial lebih dari sekadar platform bagi orang-orang untuk terhubung; itu juga merupakan alat pemasaran. Apa pun, termasuk produk kebutuhan sehari-hari, kebutuhan sekunder, filosofi, kampanye sosial, dan sebagainya, dapat diiklankan di media sosial. Instagram adalah salah satu platform media sosial yang paling populer. Popularitas Instagram di kalangan remaja merupakan fenomena yang menarik. Karena jumlah pengguna Instagram yang sangat besar di Indonesia, ada persaingan sengit untuk pengikut. Setiap konten selebgram didasarkan pada gagasan tertentu. Perbedaan tersebut merupakan jenis personal branding bagi setiap selebgram dalam menghasilkan balasan dari media sosial Instagram. Tujuan dari penelitian ini adalah untuk mempelajari bagaimana superstar Indonesia mengembangkan personal branding ‘ngondek’ mereka. Pada tiga akun, Dhanar Jabro Febiansyah (@brojabrooo), Yoga Arizona (@yogaarizona), dan Abdul Kadir (@d kadoor), penelitian ini menggunakan metodologi analisis isi kualitatif. Hasil penelitian ini menunjukkan bahwa personal branding yang dibangun oleh selebgram melalui kesan ‘Ngondek’ dapat menjadi pendekatan yang tepat dalam menarik perhatian netizen di media sosial. Tentunya dalam membangun personal branding ‘Ngondek’ tersebut juga menuntut adanya riset para selebgram ‘Ngondek’ dalam pemilihan karakter, persiapan kostum, konsep cerita, dan persiapan properti.Kata Kunci: Kebancian, merek pribadi, media sosial